Cody

# Problem 752. Is X a Fibonacci Matrix?

Solution 192388

Submitted on 17 Jan 2013 by Aurelien Queffurust
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
%% x = [0 1;1 1]; tf = true; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

2   Pass
%% x = [1 0;1 1]; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

3   Pass
%% x = [0 1;1 1]^40; tf = true; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

4   Pass
%% x = [0 1;1 1]^40+1; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

5   Pass
%% x = [0 1;1 1]^17; tf = true; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

6   Pass
%% x = [0 1;1 1]^17-5; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

7   Pass
%% x = [0 0 1;0 1 1;1 1 1]^3; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

8   Pass
%% x = [0 0 1;0 1 1]; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

9   Pass
%% x = [[0 1;1 1]^3 [5; 8]]; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

10   Pass
%% x = uint8([0 1; 1 1]^5); tf = true; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

11   Pass
%% x = -([0 1; 1 1]^5); tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

12   Pass
%% x = [0 1; 1 1]^5; x(2) = nan; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

13   Pass
%% x = [4 7;7 11]; tf = false; assert(isequal(isFibMat(x),tf)) clear all;

y = 0 1 1 1

14   Pass
%% for ii = 1:55 assert(true==isFibMat([0 1;1 1]^ii)) end

y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1 y = 0 1 1 1